Research on optimum extended phase-shift control with minimum peak-to-peak current of DAB converter applied to small DC power grid - Shi, Shuhuai; Du, Junli; Xia, Binbing; Xia, Dawei; Guan, Honglu; Wang, Feng (Frontiers in Energy Research, 2023)
The Dual Active Bridge (DAB) DC-DC converter has the ability of bidirectional power transmission and the modulation scheme that is easy to implement, which can ensure the efficient transmission of energy in the system. Therefore, it is often used in various scenarios of small DC grid, such as energy storage, photovoltaic system, electric vehicle charging and so on. The main methods to improve the efficiency of dual active bridge include reducing the effective value of current and widening the soft switching area. Based on the above idea, an optimized extended phase-shift (EPS) modulation strategy is proposed in this paper. The modulation strategy achieves the goal of reducing the effective value of the current through the constraint optimization of the corresponding variables, and then improves the efficiency of the converter. In this paper, the working principles of several typical modulation strategies are introduced in detail, and then the power characteristics and soft-switching characteristics of the new method and other commonly used modulation schemes are analyzed and compared. Finally, the effectiveness of the optimization method for extended phase-shift modulation strategy is verified by the dual active bridge experimental prototype.